Information systems control journal - Information Systems Audit and Control Association (Rolling Meadows, Ill. : Information Systems Audit and Control Association, 1979)
"A leader in IT governance and assurance."
Title from cover.
Latest issue consulted: Vol. 2 2000.
Keywords: Electronic data processing departments -- Auditing -- Periodicals; Information storage and retrieval systems -- Accounting -- Periodicals; EDP-audit.